2006
DOI: 10.1007/s10535-006-0091-4
|View full text |Cite
|
Sign up to set email alerts
|

Changes in abscisic acid and flower pigments during floral senescence of petunia

Abstract: The present work was focused on abscisic acid (ABA) changes in three differently coloured petunias during flower development and senescence. The ABA content was studied in correlation with changes of flower pigments and other phytohormones. The variations of anthocyanins and endogenous hormones were induced by treatments with 1 or 2 mM amino-oxyacetic acid (AOA), 50, 100 μM thidiazuron (TDZ) and 50 μM 6-benzyladenine (BA). ABA content decreased during bud development and increased during senescence. The AOA re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…During floral development the carotenoid concentration decreased. Petunia senescing petals also contain lower levels of carotenoids compared with flower buds . Not only the concentrations of carotenoids are subjected to changes, but also principal component analysis demonstrated that significant differences exist between the metabolic profiles of flowers of different developmental stages …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…During floral development the carotenoid concentration decreased. Petunia senescing petals also contain lower levels of carotenoids compared with flower buds . Not only the concentrations of carotenoids are subjected to changes, but also principal component analysis demonstrated that significant differences exist between the metabolic profiles of flowers of different developmental stages …”
Section: Resultsmentioning
confidence: 99%
“…Petunia senescing petals also contain lower levels of carotenoids compared with flower buds. 13 Table 2). that significant differences exist between the metabolic profiles of flowers of different developmental stages.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is possible because many of these pigments, such as anthocyanins and carotenoids, are potent antioxidants and protect the cells from the damage caused by senescence. Higher anthocyanin content is associated with longer flower life in petunia (Ferrante et al , 2006). …”
Section: Introductionmentioning
confidence: 99%